Automatic solid-phase synthesis of molecularly imprinted nanoparticles (MIP NPs) - Poma, Alessandro (Cranfield University, 2012)
Molecularly Imprinted Polymers (MIPs) are potential generic alternatives to antibodies in diagnostics and separations. To compete with biomolecules in these technological niches, MIPs need to share the characteristics of antibodies (solubility, size, specificity and affinity) whilst maintaining the advantages of MIPs (low cost, short development time and high stability). For this reason the interest in preparing MIPs as nanoparticles (MIP NPs) has increased exponentially in the last decade. Cont/d.
Keywords: Molecular imprinting; immobilised template; affinity separation; chemical reactor; antibody mimics; diagnostics